Spółdzielczość w gospodarce rynkowej - Romanow, Zbigniew (Wydział Prawa i Administracji UAM, 1995)
The paper first mentions those who initiated and propagated the idea of cooperatives, the types of cooperatives and their evolution in the market economy. Next, it stresses that despite the tendency to carry out mass privatisation and the negative evaluation which cooperatives set up in socialist countries have received, one should not overlook the positive aspects and opportunities which cooperatives create and which should therefore be given some room in economic activity. In the Polish environment the restructuring of the present cooperative system requires a new set of legal regulations defining its role and the principles according to which it operates. First of all, cooperative attitudes and relations promoting a system in which cooperatives collaborate and help one another in the market should be established. This will improve the functioning of cooperatives in the competitive market economy. Cooperatives should base their operations on principles of good management and income value which is the best measure of performance as a function of a goal, a criterion used in the assessment of any economic activity. To be successful, the restructuring of cooperatives requires, at least in its initial stage, external support of the state. This helps them to achieve independence and efficiency. It also needs to be supported by a set of organisational and economic assumptions and regulations adequate to its role assumed in the state's policy. However, the pro-cooperative policy of the state should not merely provide a protective umbrella and tolerate poor management, inefficiency and a policy of the so-called profitable minimum prices. The state's involvement should never interfere with the principles of market economy.
Cooperatives in a market economy